RESEPSI GEN Z MUSLIM TERHADAP PERPRES NO 10 TAHUN 2021 TENTANG INVESTASI MIRAS DI INDONESIA - Darlin Rizki; Zakiyatul Fakhiroh; Rifan Madani (IAIN Ambon, 2022)
Government policy issued Presidential Decree no. 10 of 2021 concerning the Investment Business Sector has drawn various controversies in the community, in Appendix III contains the legalization of alcohol investment in four provinces, Bali, NTT, North Sulawesi, and Papua. This study aims to determine the reception of Gen Z Muslims to the Presidential Decree regarding alcohol investment. This study uses a descriptive qualitative method with reception analysis, data obtained through interview and documentation studies, then analysis to determine the acceptance of informants to three positions, namely Dominant-Hegemonic Position, Negotiated Position, and Oppositional Position. The results of the study found that in the Dominant-Hegemonic Position, one informant thought that this policy could be applied, where the informant viewed Sopi or Lare as part of traditional traditions. In addition, alcohol is an important part of the community's economy. Second Negotiation Position, three informants agreed with certain conditions, such as consideration of economic recovery, caring for local culture, and alternative investments in other fields. Third Opposition Position, four informants absolutely reject the regulation. Of these three receptions, the Negotiation Position is considered the most representative of the ideal attitude according to the reception approach. This research can be used as a reference for the government in making policies. In addition, it is also useful for religious groups, practitioners, business actors, investors, and the public to know the reception of Gen Z Muslims in special areas for the implementation of alcohol investment.Keywords: Reception Analysis, Alcohol Investment, Gen Z, Controversy